(untitled) (Biological Sciences - PJSIR, 2004)
About 500 tons of industrial wastes (liquid and solid) being discharged daily from sugar factory during crushing season and presently dumped in vicinity of the sugar factory. The quantity of wastes, however, depends on the crushing capacity of sugar mills. Studies for recycling and composting of sugarcane industrial waste press mud, boiler ash and distillery waste water, as a biofertilizer, was carried out at Habib Sugar Mills Ltd., Nawabshah, Sindh, Pakistan. Samples of waste were collected for analysis from dumping ground. By mixing the heaps of press mud and boiler ash, 3:1 ratio was formed. Each heap was sprinkled with distillery waste water for two months with regular interval of one day. Two manual turning of heaps were done to maintain the temperature during the curing period and thereafter allowed for 3 months for decom- position and humus formation. Based on physico-chemical analysis of finished product, it is estimated that each ton of biofertilizer contains value-added nutrient of Rs.2897/= when compared with chemical fertilizer other than the soil amend- ment characteristic. The cost effectiveness of the biofertilizer for millers and farmers were about Rs.1:4 and Rs.1:12, respectively.